Six-years survival and predictors of mortality after CABG using cold vs. warm blood cardioplegia in elective and emergent settings - Zeriouh, Mohamed (J Cardiothorac Surg, 2015)
BACKGROUND: The aim of this study was to determine whether intermittent warm blood cardioplegia (IWC) is associated with comparable myocardial protection compared to cold blood cardioplegia (ICC) in patients undergoing elective vs. emergent CABG procedures. METHODS: Out of 2292 consecutive patients who underwent isolated on-pump CABG surgery using cardioplegic arrest either with ICC or IWC between January 2008 and December 2010, 247 consecutive emergent patients were identified and consecutively matched 1:2 with elective patients based on gender, age (<50 years, 50–70 years, >70 years) and ejection fraction (<40 %, 40–50 %, >50 %). Perioperative outcomes and long-term mortality were compared between ICC and IWC strategies and predictors for 30-day mortality and perioperative myocardial injury were identified in both elective and emergent subgroups of patients. RESULTS: Preoperative demographics and baseline characteristics, logistic Euroscore, CPB-time, number of distal anastomoses and LIMA-use were comparable. Aortic cross clamp time was significantly longer in the IWC-group regardless of the urgency of the procedure (p = 0.05 and p = 0.015 for emergent and elective settings). There were no significant differences regarding ICU-stay, ventilation time, total blood loss and need for dialysis. The overall 30-day, 1-, 3- and 6-year survival of the entire patient cohort was 93.7, 91.8, 90.4 and 89.1 %, respectively, with significantly better outcomes when operated electively (p < 0.001) but no differences between ICC and IWC both in elective (p = 0.857) and emergent (p = 0.741) subgroups. Multivariate analysis did not identify the type of cardioplegia as a predictor for 30-day mortality and for perioperative myocardial injury. However, independent factors predictive of 30-day mortality were: EF < 40 % (OR 3.66; 95 % CI: 1.79–7.52; p < 0.001), atrial fibrillation (OR 3.33; 95 % CI: 1.49-7.47; p < 0.003), peripheral artery disease (OR 2.51; 95 % CI: 1.13–5.55; p < 0.023) and COPD (OR 0.26; 95 % CI: 1.05–6.21; p < 0.038); predictors for perioperative myocardial infarction were EF < 40 % (OR 2.04; 95 % CI: 1.32–3.15; p < 0.001), preoperative IABP support (OR 3.68; 95 % CI: 1.34-10.13; p < 0.012), and hemofiltration (OR 3.61; 95 % CI: 2.22–5.87; p < 0.001). CONCLUSION: Although the aortic cross clamp time was prolonged in the IWC group our results confirm effective myocardial protection under IWC, regardless of the urgency of the procedure. We suggest that intermittent warm cardioplegia in emergent CABG setting is a low-cost alternative and safe. It is associated with similar long-term outcomes both in elective and emergent settings compared to intermittent cold cardioplegia.